Catalyst for hydrogenation of hydroxypivalaldehyde to pivalinol and method of preparation

CN117983307BActive Publication Date: 2026-10-27WUHUAN ENG +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311800377.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2026-10-27
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

但金属有机框架材料存在可加工性差、成型难度大的缺点,极大限制了其实际应用

Benefits of technology

[0024]1)活性金属Cu于MIL-101孔道内分布均匀、晶粒更小,裸露的Cu原子多、活性高,同时,Cu晶粒被限域于MIL-101孔道内,在反应过程中不易移位、团聚、流失,从而稳定性好;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a catalyst for preparing neopentyl glycol by hydroxyl neopentyl aldehyde hydrogenation and a preparation method thereof, and the catalyst is Cu-MIL-101 / Al2O3, MIL-101 is coated on Al2O3, and Cu atom clusters are encapsulated in the MIL-101 channel. The Cu is uniformly distributed in the MIL-101 channel, the crystal grain is smaller, the exposed Cu atom is more, the activity is higher, the Cu crystal grain is limited in the MIL-101 channel, and the Cu crystal grain is not easy to shift, agglomerate and flow in the reaction process, so that the stability is good; the MIL-101 has high porosity and large specific surface area, has excellent adsorption and storage capacity for H2, forms high-concentration hydrogen-rich in the catalyst channel, and can effectively promote the hydrogenation reaction; the alpha-Al2O3 has the advantages of good heat resistance, good formability, stable crystal phase, high mechanical strength and the like, and the material formed by coating the MIL-101 on the alpha-Al2O3 has the advantages of high strength, good formability and high specific surface area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst production and preparation technology, specifically relating to a catalyst and its preparation method for the hydrogenation of hydroxypentanal to neopentyl glycol. Background Technology

[0002] Neopentyl glycol is an important chemical intermediate. It is mainly used in the production of unsaturated resins, polyester powder coatings, oil-free alkyd resins, polyurethane foams, elastomers, as a plasticizer, synthetic plasticizer, surfactant, insulating materials, printing inks, polymerization inhibitors, and additives for synthetic aviation lubricants. It also has applications in the pharmaceutical industry. Furthermore, neopentyl glycol is an excellent solvent, used for the selective separation of aromatics and cycloalkyl hydrocarbons.

[0003] Neopentyl glycol is typically synthesized industrially using two processes: disproportionation and condensation hydrogenation. Condensation hydrogenation is the mainstream process for synthesizing neopentyl glycol. Formaldehyde and isobutyraldehyde are synthesized into hydroxyneopental under the action of an organic amine catalyst. Then, hydroxyneopental is hydrogenated to obtain the final product, neopentyl glycol. This method is an advanced and environmentally friendly process, as the catalyst can be recycled, resulting in less pollution, lower formaldehyde consumption, and higher quality neopentyl glycol.

[0004] The catalyst for the hydrogenation of hydroxypentylaldehyde to neopentyl glycol is one of the main challenges in the industrialization of condensation hydrogenation processes. Hydroxypentylaldehyde hydrogenation catalysts are mainly nickel-based, copper-based, and noble metal catalysts. Compared with nickel-based and noble metal catalysts, copper-based catalysts have advantages such as high activity and selectivity, and low cost in the HPA hydrogenation reaction. Most publicly reported hydroxypentylaldehyde hydrogenation catalysts are copper-based metal oxide catalysts. Catalysts containing cobalt, copper, manganese, and nickel, as disclosed in US3808280, and those using Cu-Zn-Al or Cu-Zn-Al-Mn catalysts, as well as the Cu-Zn-Al-Zr-Re catalyst disclosed in CN201110187555.8, CN201110187553.9, and CN201110187537.X, are all metal oxide system catalysts, mostly prepared by co-precipitation. This system of catalysts has the advantage of high activity, but because the hydrogenation of hydroxyneoprenedialdehyde is an exothermic reaction, the active metal Cu crystals will gradually agglomerate and grow due to the heat of reaction during the long reaction period, thus gradually becoming deactivated.

[0005] Metal-organic frameworks (MOFs) are porous crystalline materials composed of inorganic metal ions and organic ligands linked by coordination bonds. They possess characteristics such as high specific surface area, high porosity, tunable pore size, and functionality, showing promise in fields such as gas storage, catalysis, drug delivery, and separation processes. MIL-101 is one of the classic structures, featuring a high specific surface area, large-pore three-dimensional channels, and good thermal stability, withstanding temperatures up to 300°C. However, MOF materials suffer from poor processability and difficult molding, which greatly limits their practical applications. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a catalyst and preparation method for the hydrogenation of hydroxypentanal to neopentyl glycol that has good formability, high strength, good activity, and stable performance.

[0007] To achieve the above objectives, the present invention provides a catalyst for the hydrogenation of hydroxypentylaldehyde to neopentyl glycol, wherein the catalyst is Cu-MIL-101 / Al2O3, MIL-101 is coated on Al2O3, and Cu atom clusters are encapsulated in the pores of MIL-101.

[0008] Furthermore, the mass ratio of MIL-101 to Al2O3 is 0.5 to 2.

[0009] Furthermore, the mass of Cu is 5-15% of the total mass of the catalyst.

[0010] Furthermore, the Al2O3 is selected from α-Al2O3 powder.

[0011] A method for preparing the catalyst as described above is also provided as follows:

[0012] 1) To remove metal ions Cr 3+ MIL-101 / Al2O3 was prepared by hydrothermal reaction of terephthalic acid and α-Al2O3 after being stirred evenly.

[0013] 2) Cu was impregnated into MIL-101 / Al2O3 using a dual-solvent method, and then dried and reduced to obtain the catalyst Cu-MIL-101 / Al2O3.

[0014] Furthermore, the specific process of step 1) is as follows:

[0015] 1a) Chromium nitrate and terephthalic acid are dissolved in an aqueous solution, acetic acid and α-Al2O3 are added and stirred evenly, and the mixture is reacted in a high-pressure hydrothermal reactor at a reaction temperature of 160-240℃ for 8-16 hours. After cooling to room temperature, the mixture is removed and filtered to obtain a solid material.

[0016] Among them, the metal ions Cr in the aqueous solution 3+The molar ratio of terephthalic acid and water is 1:1:260, and the amount of acetic acid added is 5-15% of the mass of the aqueous solution.

[0017] 1b) Wash the solid material from step 1) sequentially with N,N-dimethylformamide (DMF) and methanol for 12–16 hours;

[0018] 1c) The solid material washed in step 1b) is placed in a vacuum oven and dried at 40-70°C for 12-16 hours to obtain MIL-101 / Al2O3. The drying temperature is 40-70°C.

[0019] Furthermore, the specific process of step 2) is as follows:

[0020] 2a) Disperse MIL-101 / Al2O3 into n-hexane, and add copper nitrate solution dropwise under stirring. After the addition is complete, continue stirring at room temperature for 2-5 hours.

[0021] 2b) After stirring, filter out the solid material and place it in a vacuum oven to dry at 60-120°C for 8-16 hours.

[0022] 2c) The solid material dried in step 2b) is reduced with 1-5% H2 / 99-95% N2 reducing gas at a reduction temperature of 200-260℃ for 3-12 hours. After the reduction is completed, the catalyst Cu-MIL-101 / Al2O3 is obtained.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0024] 1) The active metal Cu is evenly distributed in the MIL-101 channels with smaller grains, more exposed Cu atoms and high activity. At the same time, the Cu grains are confined in the MIL-101 channels, which makes them less prone to displacement, agglomeration and loss during the reaction, thus resulting in good stability.

[0025] 2) MIL-101 has high porosity and large specific surface area, and has excellent adsorption and storage capacity for H2, forming a high concentration of hydrogen-rich material in the catalyst channels, which can effectively promote the hydrogenation reaction.

[0026] 3) α-Al2O3 has advantages such as good heat resistance, good formability, stable crystal phase and high mechanical strength. The material formed by coating MIL-101 on it also has the advantages of high strength, good formability and high specific surface area. In addition, α-Al2O3 is an excellent heat conductor. When combined with MIL-101 which has a three-dimensional pore structure, it can quickly conduct reaction heat and avoid heat accumulation at the reactive sites, which would affect the stability of MIL-101 material. Detailed Implementation

[0027] To make the objectives and advantages of the present invention clearer, the present invention will be specifically described below with reference to the embodiments. The salts used in the comparative examples and embodiments are calculated to be 100% pure.

[0028] Comparative Example

[0029] 5.62 g of copper nitrate trihydrate and 62.52 g of aluminum nitrate nonahydrate were dissolved in deionized water to prepare a solution with a salt concentration of 1 mol / L. The solution was then co-precipitated with a 1 mol / L sodium carbonate aqueous solution to prepare a catalyst. During the precipitation process, the temperature of the reaction solution was controlled at 80℃ and the pH at 7.5. The mixture was stirred continuously. After the salt and alkali were added dropwise, the solution was aged for 2 hours. After washing, drying, and calcining, the solution was reduced with a 5% H2 / N2 mixed gas at a reduction temperature of 200℃ to obtain catalyst 15Cu / Al2O3.

[0030] Example 1

[0031] Dissolve 3.13g of chromium nitrate nonahydrate and 1.3g of terephthalic acid in 36.67g of water, add 2.0g of acetic acid, and then add 6.33g of Al2O3. Place the mixture in a high-pressure hydrothermal reactor and react at 240℃ for 8 hours. After cooling to room temperature, filter out the solid material.

[0032] The obtained solid material was washed in 100 ml DMF for 12 h, filtered, and then washed in 100 ml methanol for 12 h. After filtration, the solid material was placed in a vacuum oven and dried at 60 °C for 12 h to obtain dried MIL-101 / Al2O3-1.

[0033] The obtained MIL-101 / Al2O3-1 was dispersed in 100 ml of n-hexane; 1.87 g of copper nitrate trihydrate was dissolved in 6.5 g of water to obtain a salt solution. The obtained salt solution was added dropwise to the MIL-101 / Al2O3-1 suspension while stirring was started. The addition time was 10 min, and then stirring was continued for 2 h. After filtering out the solid material, it was placed in an 80 ℃ oven to dry for 10 h.

[0034] The dried solid material was placed in a tube furnace, and a mixture of 5% H2 / 95% N2 gas was introduced. The temperature was increased to 200℃ at a rate of 3℃ / min. After reduction for 6 hours, the temperature was lowered to obtain the catalyst 5Cu-MIL-101 / Al2O3-1.

[0035] Example 2

[0036] Dissolve 4.7g of chromium nitrate nonahydrate and 2.0g of terephthalic acid in 55.0g of water, add 5.65g of acetic acid, and then add 4.75g of Al2O3. Place the mixture in a high-pressure hydrothermal reactor and react at 160℃ for 16h. After cooling to room temperature, filter out the solid material.

[0037] The obtained solid material was washed in 100 ml of DMF for 12 h, filtered, and then washed in 100 ml of methanol for 12 h. After filtration, the solid material was placed in a vacuum oven and dried at 70 °C for 12 h to obtain dried MIL-101 / Al2O3-2.

[0038] The obtained MIL-101 / Al2O3-2 was dispersed in 100 ml of n-hexane; 1.87 g of copper nitrate trihydrate was dissolved in 10.0 g of water to obtain a salt solution. The obtained salt solution was added dropwise to the MIL-101 / Al2O3-2 suspension while stirring was started. The addition time was 15 min, and then stirring was continued for 3 h. After filtering out the solid material, it was placed in an 80 ℃ oven to dry for 16 h.

[0039] The dried solid material was placed in a tube furnace, and a mixture of 5% H2 / 95% N2 gas was introduced. The temperature was increased to 220°C at a rate of 3°C / min. After reduction for 6 hours, the temperature was lowered to obtain the catalyst 5Cu-MIL-101 / Al2O3-2.

[0040] Example 3

[0041] Dissolve 5.35g of chromium nitrate nonahydrate and 2.22g of terephthalic acid in 62.5g of water, add 4.0g of acetic acid, and then add 3.6g of Al2O3. Place the mixture in a high-pressure hydrothermal reactor and react at 160℃ for 16h. After cooling to room temperature, filter out the solid material.

[0042] The obtained solid material was washed in 100 ml DMF for 15 h, filtered, and then washed in 100 ml methanol for 15 h. After filtration, the solid material was placed in a vacuum oven and dried at 40 °C for 16 h to obtain dried MIL-101 / Al2O3-3.

[0043] The obtained MIL-101 / Al2O3-3 was dispersed in 100 ml of n-hexane; 3.75 g of copper nitrate trihydrate was dissolved in 11.0 g of water to obtain a salt solution. The obtained salt solution was added dropwise to the MIL-101 / Al2O3-3 suspension while stirring was started. The addition time was 20 min, and then stirring was continued for 4 h. After filtering out the solid material, it was placed in an oven at 100 ℃ and dried for 8 h.

[0044] The dried solid material was placed in a tube furnace, and a mixture of 5% H2 / 95% N2 gas was introduced. The temperature was increased to 240°C at a rate of 3°C / min. After reduction for 8 hours, the temperature was lowered to obtain catalyst 10Cu-MIL-101 / Al2O3-3.

[0045] Example 4

[0046] Dissolve 5.61g of chromium nitrate nonahydrate and 2.33g of terephthalic acid in 65.6g of water, add 11.0g of acetic acid, and then add 2.83g of Al2O3. Place the mixture in a high-pressure hydrothermal reactor and react at 240℃ for 16h. After cooling to room temperature, filter out the solid material.

[0047] The obtained solid material was washed in 100 ml DMF for 16 h, filtered, and then washed in 100 ml methanol for 16 h. After filtration, the solid material was placed in a vacuum oven and dried at 70 °C for 16 h to obtain dried MIL-101 / Al2O3-4.

[0048] The obtained MIL-101 / Al2O3-4 was dispersed in 100 ml of n-hexane; 5.62 g of copper nitrate trihydrate was dissolved in 11.2 g of water to obtain a salt solution. The obtained salt solution was added dropwise to the MIL-101 / Al2O3-4 suspension while stirring was started. The addition time was 20 min, and then stirring was continued for 5 h. After filtering out the solid material, it was placed in an oven at 120 ℃ and dried for 16 h.

[0049] The dried solid material was placed in a tube furnace, and a mixture of 5% H2 and 95% N2 gas was introduced. The temperature was increased to 220°C at a rate of 3°C / min. After reduction for 12 hours, the temperature was lowered to obtain catalyst 15Cu-MIL-101 / Al2O3-4.

[0050] Example 5

[0051] Dissolve 4.05g of chromium nitrate nonahydrate and 1.68g of terephthalic acid in 47.3g of water, add 4.86g of acetic acid, and then add 5.11g of Al2O3. Place the mixture in a high-pressure hydrothermal reactor and react at 180℃ for 12h. After cooling to room temperature, filter out the solid material.

[0052] The obtained solid material was washed in 100 ml DMF for 14 h, filtered, and then washed in 100 ml methanol for 14 h. After filtration, the solid material was placed in a vacuum oven and dried at 40 °C for 16 h to obtain dried MIL-101 / Al2O3-5.

[0053] The obtained MIL-101 / Al2O3-5 was dispersed in 100 ml of n-hexane; 3.00 g of copper nitrate trihydrate was dissolved in 8.3 g of water to obtain a salt solution. The obtained salt solution was added dropwise to the MIL-101 / Al2O3-5 suspension while stirring was started. The addition time was 10 min, and then stirring was continued for 2 h. After filtering out the solid material, it was placed in a 60 ℃ oven to dry for 16 h.

[0054] The dried solid material was placed in a tube furnace, and a mixture of 5% H2 / 95% N2 gas was introduced. The temperature was increased to 240°C at a rate of 3°C / min. After reduction for 3 hours, the temperature was lowered to obtain the catalyst 8Cu-MIL-101 / Al2O3-5.

[0055] Example 6

[0056] Dissolve 5.6g of chromium nitrate nonahydrate and 2.33g of terephthalic acid in 65.51g of water, add 6.72g of acetic acid, and then add 3.14g of Al2O3. Place the mixture in a high-pressure hydrothermal reactor and react at 220℃ for 16h. After cooling to room temperature, filter out the solid material.

[0057] The obtained solid material was washed in 100 ml DMF for 16 h, filtered, and then washed in 100 ml methanol for 16 h. After filtration, the solid material was placed in a vacuum oven and dried at 50 °C for 16 h to obtain dried MIL-101 / Al2O3-6.

[0058] The obtained MIL-101 / Al2O3-6 was dispersed in 100 ml of n-hexane; 4.49 g of copper nitrate trihydrate was dissolved in 11.44 g of water to obtain a salt solution. The obtained salt solution was added dropwise to the MIL-101 / Al2O3-6 suspension while stirring was started. The addition time was 20 min, and then stirring was continued for 4 h. After filtering out the solid material, it was placed in an oven at 100 ℃ and dried for 10 h.

[0059] The dried solid material was placed in a tube furnace, and a mixture of 5% H2 / 95% N2 gas was introduced. The temperature was increased to 260°C at a rate of 3°C / min. After reduction for 12 hours, the temperature was lowered to obtain catalyst 12Cu-MIL-101 / Al2O3-6.

[0060] Example 7

[0061] Dissolve 5.08g of chromium nitrate nonahydrate and 2.11g of terephthalic acid in 59.37g of water, add 6.65g of acetic acid, and then add 4.27g of Al2O3. Place the mixture in a high-pressure hydrothermal reactor and react at 180℃ for 12h. After cooling to room temperature, filter out the solid material.

[0062] The obtained solid material was washed in 100 ml DMF for 14 h, filtered, and then washed in 100 ml methanol for 14 h. After filtration, the solid material was placed in a vacuum oven and dried at 60 °C for 14 h to obtain dried MIL-101 / Al2O3-7.

[0063] The obtained MIL-101 / Al2O3-7 was dispersed in 100 ml of n-hexane; 2.25 g of copper nitrate trihydrate was dissolved in 10.78 g of water to obtain a salt solution. The obtained salt solution was added dropwise to the MIL-101 / Al2O3-7 suspension while stirring was started. The addition time was 15 min, and then stirring was continued for 5 h. After filtering out the solid material, it was placed in an 80 ℃ oven to dry for 12 h.

[0064] The dried solid material was placed in a tube furnace, and a mixture of 5% H2 / 95% N2 gas was introduced. The temperature was increased to 210°C at a rate of 3°C / min. After reduction for 5 hours, the temperature was lowered to obtain the catalyst 6Cu-MIL-101 / Al2O3-7.

[0065] Example 8

[0066] Dissolve 4.46g of chromium nitrate nonahydrate and 1.85g of terephthalic acid in 52.11g of water, add 4.67g of acetic acid, and then add 4.5g of Al2O3. Place the mixture in a high-pressure hydrothermal reactor and react at 160℃ for 16h. After cooling to room temperature, filter out the solid material.

[0067] The obtained solid material was washed in 100 ml DMF for 14 h, filtered, and then washed in 100 ml methanol for 14 h. After filtration, the solid material was placed in a vacuum oven and dried at 50 °C for 12 h to obtain dried MIL-101 / Al2O3-8.

[0068] The obtained MIL-101 / Al2O3-8 was dispersed in 100 ml of n-hexane; 3.75 g of copper nitrate trihydrate was dissolved in 9.06 g of water to obtain a salt solution. The obtained salt solution was added dropwise to the MIL-101 / Al2O3-8 suspension while stirring was started. The addition time was 15 min, and then stirring was continued for 3 h. After filtering out the solid material, it was placed in a 90 ℃ oven to dry for 8 h.

[0069] The dried solid material was placed in a tube furnace, and a mixture of 5% H2 / 95% N2 gas was introduced. The temperature was increased to 250°C at a rate of 3°C / min. After reduction for 8 hours, the temperature was lowered to obtain catalyst 10Cu-MIL-101 / Al2O3-8.

[0070] Example 9

[0071] Dissolve 5.30g of chromium nitrate nonahydrate and 1.85g of terephthalic acid in 52.11g of water, add 10.42g of acetic acid, and then add 3.35g of Al2O3. Place the mixture in a high-pressure hydrothermal reactor and react at 220℃ for 16h. After cooling to room temperature, filter out the solid material.

[0072] The obtained solid material was washed in 100 ml DMF for 14 h, filtered, and then washed in 100 ml methanol for 14 h. After filtration, the solid material was placed in a vacuum oven and dried at 60 °C for 16 h to obtain dried MIL-101 / Al2O3-9.

[0073] The obtained MIL-101 / Al2O3-9 was dispersed in 100 ml of n-hexane; 4.87 g of copper nitrate trihydrate was dissolved in 10.69 g of water to obtain a salt solution. The obtained salt solution was added dropwise to the MIL-101 / Al2O3-9 suspension while stirring was started. The addition time was 20 min, and then stirring was continued for 4 h. After filtering out the solid material, it was placed in an 80 ℃ oven to dry for 14 h.

[0074] The dried solid material was placed in a tube furnace, and a mixture of 5% H2 / 95% N2 gas was introduced. The temperature was increased to 240°C at a rate of 3°C / min. After reduction for 10 hours, the temperature was lowered to obtain catalyst 13Cu-MIL-101 / Al2O3-9.

[0075] Example 10

[0076] Dissolve 4.91g of chromium nitrate nonahydrate and 2.04g of terephthalic acid in 57.41g of water, add 7.72g of acetic acid, and then add 3.54g of Al2O3. Place the mixture in a high-pressure hydrothermal reactor and react at 200℃ for 12h. After cooling to room temperature, filter out the solid material.

[0077] The obtained solid material was washed in 100 ml DMF for 16 h, filtered, and then washed in 100 ml methanol for 16 h. After filtration, the solid material was placed in a vacuum oven and dried at 50 °C for 15 h to obtain dried MIL-101 / Al2O3-10.

[0078] The obtained MIL-101 / Al2O3-10 was dispersed in 100 ml of n-hexane; 5.62 g of copper nitrate trihydrate was dissolved in 9.65 g of water to obtain a salt solution, and the obtained salt solution was added dropwise to the MIL-101 / Al2O3-10 suspension while stirring was started. The addition time was 15 min, and then stirring was continued for 4 h. After filtering out the solid material, it was placed in a 60 ℃ oven to dry for 16 h.

[0079] The dried solid material was placed in a tube furnace, and a mixture of 5% H2 / 95% N2 gas was introduced. The temperature was increased to 220°C at a rate of 3°C / min. After reduction for 16 hours, the temperature was lowered to obtain catalyst 15Cu-MIL-101 / Al2O3-10.

[0080] The catalyst activity was evaluated using a fixed-bed reactor. After molding, the catalyst was crushed into 20-40 mesh pieces and loaded into the isothermal zone of the reactor, with quartz sand filling both the top and bottom. The feedstock ratio for the hydrogenation of hydroxypentylaldehyde (HPA) to NPG was 20 wt% HPA, 40 wt% NPG, and 40 wt% H₂O. The reaction conditions were 3 MPa, 100 °C, and a HPA liquid space velocity of 0.3 h⁻¹. -1 The hydrogen-to-ester ratio is 20. The activities of each catalyst are shown in the table below.

[0081] Table 1 Catalyst Activity Test Data

[0082] Comparative Example 15Cu / Al2O3 95.20 97.10 Example 1 5Cu-MIL-101 / Al2O3-1 96.10 98.90 Example 2 5Cu-MIL-101 / Al2O3-2 97.10 99.00 Example 3 10Cu-MIL-101 / Al2O3-3 99.20 98.70 Example 4 15Cu-MIL-101 / Al2O3-4 99.90 99.30 Example 5 8Cu-MIL-101 / Al2O3-5 98.50 98.50 Example 6 12Cu-MIL-101 / Al2O3-6 99.70 99.10 Example 7 6Cu-MIL-101 / Al2O3-7 97.20 98.40 Example 8 10Cu-MIL-101 / Al2O3-8 99.00 98.70 Example 9 13Cu-MIL-101 / Al2O3-9 99.40 99.10 Example 10 15Cu-MIL-101 / Al2O3-10 99.80 998.90

[0083] Under the same reaction conditions, stability tests were conducted using the comparative catalyst and the catalyst of Example 9. After 1000 h, the HPA conversion rate of the reaction using the comparative catalyst decreased to 86.2%, and the selectivity was 92.4%. The HPA conversion rate on the 13MIL-101 / Al2O3-9 catalyst was 99.3%, and the NPG selectivity was 99.2%, indicating good stability.

Claims

1. A catalyst for the hydrogenation of hydroxypentanal to neopentyl glycol, characterized in that: The catalyst is Cu-MIL-101 / Al2O3, with MIL-101 coated on Al2O3 and Cu atom clusters encapsulated in the channels of MIL-101; the Al2O3 is selected as α-Al2O3 powder; the mass ratio of MIL-101 to Al2O3 is 0.5~2, and the mass of Cu is 5~15% of the total mass of the catalyst.

2. A method for preparing the catalyst as described in claim 1, characterized in that: The preparation method is as follows: 1) To remove metal ions Cr 3+ MIL-101 / Al2O3 was prepared by hydrothermal reaction of terephthalic acid and α-Al2O3 after being stirred evenly. 2) Cu was impregnated into MIL-101 / Al2O3 using a dual-solvent method, and then dried and reduced to obtain the catalyst Cu-MIL-101 / Al2O3; The specific process of step 1) is as follows: 1a) Chromium nitrate and terephthalic acid are dissolved in an aqueous solution, acetic acid and α-Al2O3 are added and stirred evenly, and the mixture is reacted in a high-pressure hydrothermal reactor at a reaction temperature of 160~240℃ for 8~16h. After cooling to room temperature, the mixture is taken out and filtered to obtain a solid material. Among them, the metal ions Cr in the aqueous solution 3+ The molar ratio of terephthalic acid and water is 1:1:260, and the amount of acetic acid added is 5-15% of the mass of the aqueous solution. 1b) Wash the solid material from step 1) sequentially with N,N-dimethylformamide and methanol for 12-16 hours; 1c) The solid material washed in step 1b) is placed in a vacuum oven and dried at 40~70℃ for 12~16h to obtain MIL-101 / Al2O3. The drying temperature is 40~70℃. The specific process of step 2) is as follows: 2a) Disperse MIL-101 / Al2O3 into n-hexane, and add copper nitrate solution dropwise under stirring. After the addition is complete, continue stirring at room temperature for 2-5 hours. 2b) After stirring, filter out the solid material and place it in a vacuum oven to dry at 60~120℃ for 8~16 hours. 2c) The solid material dried in step 2b) is reduced with 1~5% H2 / 99~95% N2 reducing gas at a reduction temperature of 200~260℃ for 3~12h. After the reduction is completed, the catalyst Cu-MIL-101 / Al2O3 is obtained.

Citation Information

Patent Citations

  • Two-step-method hydrogenation process for preparing neopentyl glycol

    CN102249854A

  • Method for preparing neopentyl glycol

    CN102304021A

  • Neopentyl glycol preparation method utilizing catalytic hydrogenation by copper zinc aluminium catalyst

    CN102311313A

  • Catalyst for preparing neopentyl glycol by hydrogenation and preparation method of catalyst

    CN102728370B

  • Manufacture of 2,2-dimethyl-1,3-dihydroxypropane

    US3808280A